2005
DOI: 10.5194/nhess-5-59-2005
|View full text |Cite
|
Sign up to set email alerts
|

On spread-<i>E<sub>s</sub></i> effects in the ionosphere before earthquakes

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects" Abstract. The spread-E s phenomenon which appears as diffusivity of the traces of sporadic E-layers on the ionogrammes of vertical sounding stations and which reflects the turbulization of the sporadic layers E s is studied in connection with earthquake preparation processes. Spread-E s data obtained at night every 15 min by the midlatitudinal vertical sounding station of the ionosphere in Dushan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…It might be possible that both the acoustic pulses and the ULF variations are caused by the same reason. It should be underlined that an increase of the number of Es-spread effects was not found for the earthquakes appearing during the time of solar activity maximum 1988-1989(Liperovsky et al, 2005. Thus one may conclude that the dissipation of the acoustic pulses at solar activity maximum increases so strongly, that before the earthquakes a remarkable modification of the turbulization of the sporadic Es-layer is not possible.…”
Section: Observational Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It might be possible that both the acoustic pulses and the ULF variations are caused by the same reason. It should be underlined that an increase of the number of Es-spread effects was not found for the earthquakes appearing during the time of solar activity maximum 1988-1989(Liperovsky et al, 2005. Thus one may conclude that the dissipation of the acoustic pulses at solar activity maximum increases so strongly, that before the earthquakes a remarkable modification of the turbulization of the sporadic Es-layer is not possible.…”
Section: Observational Resultsmentioning
confidence: 96%
“…Investigating the time of the Es-spread occurrence, for every In the works by Liperovsky et al (2000Liperovsky et al ( , 2005 and Silina et al (2001), it is shown that 1-3 days before an earthquake the probability of the observation of diffusivity of the Es-layer, that means of Es-spread, increases. Thus, in the present work the days (-2, -1) before an earthquake and the day of the earthquake (0 day) are taken to be the "seismoactive" ones.…”
Section: Observational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that seismic activity can excite lithospheric, atmospheric and ionospheric perturbations through mutual coupling effects. In particular, the ionospheric parameters have been found to be extremely sensitive to large earthquakes, which have been reported by a number of works (Leonard and Barnes Jr., 1965;Liu et al, 2001;Pisa et al, 2011;Zhao et al, 2008;Afraimovich et al, 2010;Liu et al, 2009;Pulinets and Ouzounov, 2011;Liperovsky et al, 2005;Shvets et al, 2004;Kon et al, 2011;Le et al, 2011;Parrot, 2012;Li and Parrot, 2013). However, in most situations the subtle signals induced by large earthquakes can be easily confused with background fluctuations and short-term disturbances due to solar and geomagnetic activity.…”
Section: Introductionmentioning
confidence: 89%
“…These methods include monitoring of disturbances in the lower ionosphere caused by seismic processes that precede the EQs. Due to small values of the electron concentration, it is difficult to register the disturbances in the lower ionosphere (D-layer) with ionosondes, although the disturbances of the sporadic layers in the E-region are found in connection with the forthcoming EQ (Liperovsky et al, 2005;Liperovskaya et al, 2006). At the same time, as it is known, ionospheric disturbances are well-manifested in variations of the parameters of the low frequency radio signals passing over the seismically active regions (Biagi et al, 2005;Rozhnoi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%